Pentingnya Edukasi Kebersihan dan Kesehatan untuk Menunjang Layanan yang Berkualitas di Lingkup Pariwisata - Joel Fernandes Gultom; Yonathan Hutajulu; Apri Twenty Sirait; Garry Anderson Nainggolan; Selfianus Pahabol (Lembaga Pengembangan Kinerja Dosen, 2025)
Hygiene and health education has an important role in supporting quality services in the tourism sector. With increasing awareness of the importance of sanitation and health, tourists are now more likely to choose destinations that prioritize cleanliness as part of their experience. This research aims to analyze the influence of hygiene and health education on service quality in the tourism sector, both from the perspective of industry players and tourists. The method used is literature study and interviews with tourism business actors in various regions. The research results show that consistent implementation of hygiene education can increase tourist confidence, create a safe and comfortable experience, and increase the competitiveness of tourist destinations. Therefore, integrating hygiene and health education programs into tourism management is a strategic step to support the sustainability of this industry.